1996
DOI: 10.1111/j.1476-5381.1996.tb15717.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation by locally produced luminal angiotensin II of proximal tubular sodium reabsorption via an AT1 receptor

Abstract: The concentration of angiotensin II reported in proximal tubular fluid in anaesthetized rats is considerably higher than in plasma, indicating secretion of this peptide into the tubular lumen. Shrinking split-drop micropuncture was used to examine the effect of endogenous angiotensin on sodium and water absorption in the proximal convoluted tubule. Addition of losartan, a nonpeptide AT, receptor blocker, to intratubular fluid increased fluid uptake by 15.7+3.9% (10-' M) and 24.7+9.4% (10-4 M) whereas the AT2 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 6 publications
2
6
1
Order By: Relevance
“…All three antagonists, losartan, EXP3174 and candesartan at 10 78 M decreased¯uid absorption by approximately 20%. At a higher concentration (10 75 M), both EXP3174 and candesartan decreased¯uid absorption, in contrast with previous observations that losartan at this dose increases transepithelial sodium transport (Hiranyachattada & Harris, 1996;Leyssac et al, 1997). The dose-dependent, biphasic eect of losartan is not consistent with selective blockade of luminal AT 1 receptors, and suggests that losartan at high concentrations (410 76 M) has a nonselective eect on sodium absorption.…”
Section: Discussioncontrasting
confidence: 76%
See 3 more Smart Citations
“…All three antagonists, losartan, EXP3174 and candesartan at 10 78 M decreased¯uid absorption by approximately 20%. At a higher concentration (10 75 M), both EXP3174 and candesartan decreased¯uid absorption, in contrast with previous observations that losartan at this dose increases transepithelial sodium transport (Hiranyachattada & Harris, 1996;Leyssac et al, 1997). The dose-dependent, biphasic eect of losartan is not consistent with selective blockade of luminal AT 1 receptors, and suggests that losartan at high concentrations (410 76 M) has a nonselective eect on sodium absorption.…”
Section: Discussioncontrasting
confidence: 76%
“…Samples of luminal fluid obtained by micropuncture from superficial proximal tubules have been shown to contain a nanomolar concentration of angiotensin II ( Seikaly et al ., 1990 ; Braam et al ., 1993 ; Mitchell et al ., 1997 ). Previous studies in our laboratory ( Hiranyachattada & Harris, 1996 ) and by Leyssac et al . (1997) concluded that addition of a high concentration of the AT 1 antagonist losartan (10 −5 M ) to the proximal tubule lumen enhanced fluid uptake.…”
Section: Introductionsupporting
confidence: 63%
See 2 more Smart Citations
“…Burns et al (34) showed that over 80% of the Ang II receptors found in the basolateral membrane of proximal tubules from rat and rabbit kidneys are of the AT 1 type, with the other 20% being of the AT 2 type. In general, it is accepted that the stimulatory effect of Ang II on proximal tubule Na + reabsorption is mediated by losartan-sensitive AT 1 receptors located in both luminal and basolateral membranes (15,35).…”
Section: Angiotensin Receptors Mediate the Modulation Of Na + -Atpasementioning
confidence: 99%